Finance and sustainability towards a new paradigm? : a post-crisis agenda - Sun, William, 1962-; Louche, Céline; Pérez, Roland (Critical studies on corporate responsibility, governance and sustainability, 2011)
The recent global financial crisis has indicated that the conventional dominant paradigm in finance is unable to cope with the problems of financial systems, markets, and behaviour of financial institutions, and failed to understand the proper role of finance in society and the economic system as a whole. Drawing on the recent movements of corporate social responsibility, socially responsible investing and sustainable development, this volume goes further to examine the ongoing making of financial reality towards social responsibility and sustainability, and aims at a better understanding of finance as a collective construct and endeavour embedded in societal context. Bringing together leading scholarly thinking this collection opens new avenues of comprehending corporate social responsibility, reveals mechanisms and strategies in shaping the reality of responsible finance, searches alternative approaches towards financial sustainability, and explores new thinking of coping with complex financial choice and financial risks. Moving away from the conventional financial paradigm, this volume demonstrates paradigm shifting in the financial world and provides fresh insights on how we may reshape the financial reality to enable societal betterment and prevent any future financial crisis.